OsNAC2 integrates auxin and cytokinin pathways to modulate rice root development - Mao, Chanjuan (Plant Biotechnol J, 2019)
The rice root system is important for growth. The crosstalk between auxin and cytokinin mediates root initiation and elongation. However, it remains unclear how the transcriptional network upstream of the auxin and cytokinin signalling pathways determines root development. Here, we observed that the knockdown of OsNAC2, which encodes a NAC transcription factor, increased the primary root length and the number of crown roots. OsNAC2 predominantly expressed in primary root tips, crown roots and lateral root primordia, implying it influences root development. Molecular analyses revealed that the expressions of auxin‐ and cytokinin‐responsive genes were affected in OsNAC2‐overexpressing (OsNAC2‐OX ; ON7 and ON11), RNA interference (OsNAC2‐RNAi; RNAi25 and RNAi31) and CRISPR/Cas9 plants. Additionally, OsNAC2 can directly bind to the promoters of IAA inactivation‐related genes ( GH3.6 and GH3.8), an IAA signalling‐related gene (OsARF25), and a cytokinin oxidase gene (OsCKX4). Furthermore, genetic analysis of ON11/osgh3.6 and RNAi31/osckx4 homozygote confirmed that OsCKX4 and OsGH3.6 functioned downstream of OsNAC2. The mRNA levels of CROWN ROOTLESS (CRL) genes and cyclin‐dependent protein kinase (CDK) genes increased in OsNAC2‐RNAi and OsNAC2‐cas9 lines while reduced in OsNAC2‐OX lines. Thus, we describe that OsNAC2 functions as an upstream integrator of auxin and cytokinin signals that affect CRL and CDK production to regulate cell division during root development. This novel auxin‐OsNAC2‐cytokinin model should provide a new insight into the understanding of NAC TFs and crosstalk of auxin and cytokinin pathway, and can be potentially applied in agriculture to enhance rice yields by genetic approaches.